Hubungan Motivasi Belajar Berbasis Expectancy-Value Theory dengan Hasil Belajar Pjok pada Siswa Kelas IV Sekolah Dasar di Kecamatan Cimalaka - Deddy Iqbal; Dinar Dinangsit; Encep Sudirjo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the relationship between learning motivation and learning outcomes in Physical Education, Sports, and Health (PJOK) among fourth-grade elementary school students in the Cimalaka District. The method used was a quantitative approach with a correlational design through an ex post facto method. The sample consisted of 40 students selected using a multistage sampling technique. Data collection instruments included a learning motivation questionnaire adapted from the Expectancy–Value Theory and documentation of authentic PJOK learning outcomes. The results showed a significant positive relationship between learning motivation and PJOK learning outcomes. In conclusion, learning motivation is an important factor in determining PJOK learning outcomes; therefore, strengthening expectancy and task value aspects is essential in the learning process. Keywords: Elementary School, Expectancy-Value, Learning Motivation, PJOK Learning Outcomes.